Familial Aggregation of Urinary Tract and Bone Tumors: Searching for a Syndrome - Andreas Frings; Jochen B. Geigl; Bernadette Liegl-Atzwanger; Andreas Leithner (Case Reports in Medicine)
Positive family anamnesis is an important risk factor for cancer, and therefore further investigations need to be done if familial aggregation of cancer is observed. Due to a rare combination of urinary tract and bone tumors occurring in the family presented herein we hypothesized a hereditary predisposition and thus, Li-Fraumeni syndrome was considered to be the most likely differential diagnosis. To confirm Li-Fraumeni syndrome, we set out to investigate this case by analyzing the tumor suppressor gene p53. However, taking into account all the diagnostic results obtained, Li-Fraumeni syndrome could not be confirmed, but there is still uncertainty regarding a definitive diagnosis.